Narrative Integrated Career Exploration Platform - Shahriar, Sakib; Ramesh, Jayroop; Towheed, Mohammed; Ameen, Taha; Sagahyroon, Assim; Al-Ali, A. R. (Frontiers in Education, 2022)
Career and technical education play a significant role in reducing high school and college dropouts as well providing necessary skills and opportunities to make suitable career decisions. The recent technological advances have benefited the education sector tremendously with the introduction of exciting innovations including virtual and augmented reality. The benefits of narrative-centered learning and game-based learning are well established in the literature. However, their implementation has been limited to the education sector. In this research, the design and implementation of a Narrative Integrated Career Exploration (NICE) platform is discussed. The platform contains four playable tracks allowing students to explore careers in artificial intelligence, cybersecurity, internet of things, and electronics. The tracks are carefully designed with narrative problem-solving reflecting contemporary real-world challenges. To evaluate the perceived usefulness of the platform, a case study involving university students was performed. The results clearly reflect students’ interest in narrative and game-based career exploration approaches.